Flexible denture base material: A viable alternative to conventional acrylic denture base material - J P Singh; R K Dhiman; R. P. S. Bedi; S H Girish (Wolters Kluwer Medknow Publications, 2011)
Although clinician's skills and experience play a major role in designing and fabrication of the optimum prosthodontic restorations, the selection of denture resins is equally important, especially when the patient has been using the prostheses since long. Eighteen cases who were not satisfied with their conventional acrylic dentures were selected. They were provided flexible dentures along with a questionnaire to precisely evaluate the advantages of new material. Prosthodontic planning & observations regarding this material are discussed on various parameters.